Involution of Community Empowerment in Strengthening the Household Economy of Homeless and Beggars in Topeng Village, Malang City - Anggraito Wisnu Aji; Rachmad Kristiono Dwi Susilo; Frida Kusumastuti (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2023)
One of the problems in Malang City is that there are still marginalized groups such as homelesspeople and beggars. Through the Desaku Menanti program initiated by the Ministry of SocialAffairs and managed by the Malang City P3AP2KB Social Service, they are placed in KampungTopeng to be empowered. This coaching has been going on for 4 years (starting from 2016 to2020). However, in 2019 this area had no productive activities or an involution processoccurred. This research uses a qualitative approach with ethnography. With the AGIL scheme(Adaptation, Goal-attainment, Integration, Latency) which is part of Talcott Parsons' FunctionalStructural Theory, this research produced several findings. Based on data collection abouthomeless people and beggars in Kampung Topeng. The findings of this study state that theform of empowerment involution is in the form of program unsustainability. The factors causinginvolution come from program implementation and target beneficiaries. From the programimplementer's side, it is closely related to changes in the priority scale of the agency's program,changes in the head of the agency, limited resources, deterioration of collaboration, the issue oflocation far from the city center. Meanwhile, from the community side, the culture of poverty andnon-standardized quality.